Marketing Strategy for Education Services in Integrated Islamic-Based Junior High Schools - Desi Afriwanti; Himyar Pasrizal (Universitas Islam negeri Mahmud Yunus Batusangkar, 2021)
The study aims to describe the strategy and marketing mix of education services in Integrated Islamic Junior High School (SMP-IT). The researcher used qualitative research to describe the data descriptively. Data collection techniques were observation, interviews, and documentation. The results of this study indicated that: 1) the marketing strategy in SMP-IT is to strengthen the IT and Public Relations (Humas) team in the school. 2) The marketing strategy of education services in SMP-IT is by implementing a marketing mix of products, prices, places, promotions, human resources, physical evidence and processes. The superior marketed products are tahfiz programs, language programs, Birrul Walidain and academic extracurriculars, as well as providing scholarship for excellent students. Promotion strategies are carried out through Instagram, YouTube, Twitter, Facebook, websites, and newspapers..Â